Two Worlds, Two Realities - The Social Experience of Seasonal Agricultural Workers in Quebec - Dube, Melissa (University of Ottawa (Canada), 2010)
This thesis explores the social experience of Mexican and Guatemalan temporary immigrants in Quebec who are part of the Seasonal Agricultural Workers Program (SAWP) and the Temporary Foreign Workers Program (TFWP). Two distinct perspectives exist on the matter: that the programs are beneficial for all parties involved (workers, employers, and governments); and, that the programs exploit the workers involved, who must make important sacrifices and get meagre benefits. In the literature review, a neoliberal environment is found to be a macro factor that affected the programs substantially. This thesis, based on qualitative research conducted with workers and other program participants, brings new evidence to bear on these debates. Even though the workers come to Quebec strictly to earn money for their families, the social isolation and language barrier they endure in their host communities make their lives in Canada often very difficult. While more and more activities for the workers are being organised, additional efforts could be made. This thesis concludes that, overall the experience of the workers is not poor, but there is clearly room for improvement in order to balance their significant sacrifices and the benefits they (and Canada) get from the difficult work they perform.
Keywords: Sociology, Social Structure and Development.